IMPROVING THE MATHEMATICAL CREATIVE THINKING ABILITY OF ELEMENTARY STUDENTS THROUGH THE CRH LEARNING MODEL ASSISTED BY MONOPOLY GAME MEDIA - Siti Ruqoyyah; Linda Hania Fasha; Euis Eti Rohaeti (Jurnal Ilmiah P2M STKIP Siliwangi, 2019)
This research is motivated by the students' low mathematical creative thinking abilities. The purpose of this research is to examine the achievement and improvement of students' mathematical creative thinking abilities whose learning uses the Course Review Horay (CRH) learning model assisted by monopoly game media. This research is a quasi-experimental type with pretest-posttest control group design with experimental class using Course Review Horay (CRH) learning model assisted by monopoly game media and control class using conventional learning. The population in this study were fifth-grade elementary school students in Cimahi City, while the samples were 30 students each for the experimental and control classes. Data collection techniques used are tests, observations, and documentation with data analysis using statistical data analysis. The results showed the average experimental class value of pretest reached 4.97 and the posttest reached 11.97 with an N-gain value of 0.46. While in the control class the average pretest value reached 4.50 and the posttest reached 9.70 with an N-gain value of 0.34. It can be concluded that the use of CRH learning models assisted by monopoly game media is more effective in achieving and increasing students' creative thinking abilities compared to conventional learning.